Analysis of Knowledge Construction Process in Junior High School Students Through Ethnomathematics Based Problem Solving - Nurul Izzati Ramadhan; Kamid Kamid; Yelli Ramalisa (SJME (Supremum Journal of Mathematics Education), 2025)
This study aimed to analyze knowledge construction process on the 8th grade of junior high school through mathematical problem solving based on ethnomathematics for several students with high, medium, and low problem solving abilities. We employ qualitative method to reveal the subject’s knowledge construction process. Data collection in this study was carried out by giving problem solving ability test, knowledge construction process test and interviewing 3 research subjects, one student was selected from each level of problem solving ability. Data were analyzed using data reduction, data display, and conclusion drawing. This research describes that students with high problem solving abilities in all four steps of problem solving use assimilation thinking process. Students thinking process whose problem-solving abilities is medium use assimilation thinking process in understanding the problem, creating a solution, and carrying out the plan, while reviewing the answers they use accommodation thinking process. In addition, students with low problem solving abilities in understanding the problem, use assimilation and accommodation thinking processes, in creating a solution, they use the assimilation thinking process, and use accommodation thinking process in carrying out the plan, while reviewing the answers there is imperfect accommodation thinking process